2015
DOI: 10.1016/j.bbamem.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Structural variations of the cell wall precursor lipid II in Gram-positive bacteria — Impact on binding and efficacy of antimicrobial peptides

Abstract: Antimicrobial peptides (AMPs) are natural antibiotics produced by virtually all living organisms. Typically, AMPs are cationic and amphiphilic and first contacts with target microbes involve interactions with negatively charged components of the cell envelope such as lipopolysaccharide (LPS), and wall- or lipoteichoic acids (WTA, LTA). The importance of charge-mediated interactions of AMPs with the cell envelope is reflected by effective microbial resistance mechanisms which are based on reduction of the overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 115 publications
0
81
0
Order By: Relevance
“…One of the strategies followed by several drugs is interfering with the synthesis of the peptidoglycan. An important precursor of the peptidoglycan synthesis is the lipid II, which was shown to be an attractive target of antibacterial compounds, such as AMPs [53]. In addition, a recent study also demonstrated that the precursors of peptidoglycan, lipids III and IV, are also targets.…”
Section: Most Relevant Microbial Threats To Health and Antimicrobimentioning
confidence: 99%
“…One of the strategies followed by several drugs is interfering with the synthesis of the peptidoglycan. An important precursor of the peptidoglycan synthesis is the lipid II, which was shown to be an attractive target of antibacterial compounds, such as AMPs [53]. In addition, a recent study also demonstrated that the precursors of peptidoglycan, lipids III and IV, are also targets.…”
Section: Most Relevant Microbial Threats To Health and Antimicrobimentioning
confidence: 99%
“…Unlike the Edman degradation product of vancomycin, which is devoid of any activity, des-Ori retains potent antimicrobial activities against both vancomycin-susceptible and -resistant pathogens despite the damaged D-Ala-D-Ala binding site (28,29). This activity is mediated by the secondary binding site, which allows des-Ori binding to cross-linked PG in the cell wall (4, 7), as well as increased binding affinity to lipid II that has a pentaglycine bridge attached (30).…”
Section: Discussionmentioning
confidence: 99%
“…The pentapeptide l ‐Ala‐ d ‐ γ ‐Glu‐ l ‐Lys‐ d ‐Ala‐ d ‐Ala is typically present in most Gram‐positive pathogens . Cross‐linking of the glycan chains is then achieved through side‐chain‐to‐backbone amide bond formation between strands of pentapeptide domains …”
Section: Targeting the Central Component Of Peptidoglycan Synthesismentioning
confidence: 99%
“…Bacterial cell wall biosynthesis is highly complex, with multiple components and numerous tightly coordinated enzymatic reactions (Figure ) . The two‐stage process of peptidoglycan subunit synthesis begins with the assembly of UDP‐MurNAc‐pentapeptide precursor from UDP‐GlcNAc through a series of steps catalysed by MurA‐F synthetases in cytoplasmic side .…”
Section: Targeting the Central Component Of Peptidoglycan Synthesismentioning
confidence: 99%
See 1 more Smart Citation